A life with ghosts : true, terrifying, and insightful tales from my favorite haunts - Gonsalves, Steve; Aloisi, Michael (Gallery Books, 2023)
"The paranormal investigator and star of the smash hit show Ghost Hunters TV shares a collection of his most memorable encounters and terrifying experiences with disembodied voices, mysterious dark masses, and other unexplained phenomena"--